1999
DOI: 10.1007/s007050050553
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for three groups of sequence variants of beet necrotic yellow vein virus RNA 5

Abstract: About half of Japanese isolates of beet necrotic yellow vein virus (BNYVV) were found to contain RNA 5 molecules, which were also detected in virus isolates from China and France. Sequence comparisons of RNA 5 (nucleotides 327 to 1171) in 25 isolates showed that there are up to 8% sequence differences, and that RNA 5 variants fall into three groups: group I contains most of the Japanese and Chinese isolates, group II two Japanese isolates, and group III four French isolates. The group I isolates fall into thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 10 publications
7
82
1
Order By: Relevance
“…The other six wt BNYVV isolates and their origins are listed in Table 1. Each of the virus isolates was recovered from infested soil as described previously (Miyanishi et al, 1999). The IV4, IP7, USTH and T41 isolates contained RNA1-RNA4, whilst the FP isolate contained the additional RNA5.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other six wt BNYVV isolates and their origins are listed in Table 1. Each of the virus isolates was recovered from infested soil as described previously (Miyanishi et al, 1999). The IV4, IP7, USTH and T41 isolates contained RNA1-RNA4, whilst the FP isolate contained the additional RNA5.…”
Section: Methodsmentioning
confidence: 99%
“…Sequences of RNA3 from natural BNYVV isolates were obtained as described previously (Miyanishi et al, 1999). Two specific primers, 3F (59-AGTTGTTGTGTTTTCTGATC-39, nt 4082427) and the reverse primer 3R (59-CCGTGAAATCACGTGTAGTT-39, complementary to nt 124921268) were used (Saito et al 1996).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Types A and B are distributed worldwide and contain only four RNAs. Type A is present in most European countries, Iran, North America, China and Japan, whereas type B is detected frequently in France and Germany, and in Sweden, China and Japan occasionally (SAITO et al 1996;MIYANISHI et al 1999;LENNEFORS et al 2000;SOHI and MALEKI 2004). The isolates which contain five RNAs represent type P of BNYVV and so far have been found only in France (KOENIG et al 1999), the UK (HARJU et al 2002) and also in Kazakhstan .…”
Section: Zusammenfassungmentioning
confidence: 99%
“…Our BNYVV isolates were not digested by these restriction enzymes, suggesting that the isolate from R. raphanistrum belongs to the A type strain (Figure 3). The A type, the most widespread strain (Schirmer et al, 2005), has been previously detected in Turkey (Kruse et al, 1994;Kutluk Yilmaz et al, 2007); the B type strain is more restricted and mainly found in Germany, France (Kruse et al, 1994;Koenig et al, 2008), Japan (Miyanishi et al, 1999), and China (Li et al, 2008).…”
Section: Detection Of Bnyvvmentioning
confidence: 99%